Etika Mahasiswa di Lingkungan Pendidikan - Renofa Bernadeth Pasaribu; Nainggolan, Ketrin Gresia; Noni Robintang Simbolon; Refina Betseiba Br Tarigan (Yayasan Literasi Sains Indonesia, 2024)
Ethics is something that underlies the character of students. A good student must have good ethics too. However, not all students pay attention to ethics. Nowadays, there are many issues or cases of students who lack ethics in the educational environment. Lack of respect for lecturers is often a problem of student ethics. For example, students do not pay attention when the lecturer is talking or explaining the material. Such as students who like to chat with other students with a loud enough voice, playing mobile phones, to be reprimanded by the lecturer who teaches because it disrupts learning activities and lacks respect for the lecturer who speaks. So it can be concluded that there are still students who are not ethical in an educational environment and should know and apply ethics in an educational environment. The purpose of this research is to find out how students' knowledge and application of student ethics in the educational environment. This research uses interview and observation methods. The population used in this study were DIII Nursing students, Health Information Management, with the number of sources 30 and indicators as many as 5 questions.